Pengaruh Budaya Organisasi dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Boma Tirta Prima Makassar - Adam Baranti; Suhardi M Anwar; Muh Yusuf Qamaruddin (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: This study aimed to determine the effect of organizational culture and work motivation on employee performance at PT Boma Tirta Prima Makassar. Methodology: This study is quantitative research. This study used a questionnaire to collect the research data. This study used SPSS26 as a tool for data processing. Results: Organizational culture and work motivation have a significant positive effect, both partially and simultaneously, on employee performance in PT Boma Tirta Prima Makassar. Limitations: A lack of data sources is expected in the future to conduct research in several different locations. Conclusion: Organizational culture has a significant influence on employee performance at PT. Boma Tirta Prima Makassar. Work motivation has a significant influence on employee performance at PT. Boma Tirta Prima Makassar. Organizational culture and work motivation have a significant influence simultaneously on employee performance at PT. Boma Tirta Prima Makassar. Contribution: This research is expected to be a source of reference for further research and a consideration for PT Boma Tirta Prima Makassar as a reference for improving employee performance.